2020
DOI: 10.3389/fsufs.2020.606828
|View full text |Cite
|
Sign up to set email alerts
|

Production of Microsclerotia From Entomopathogenic Fungi and Use in Maize Seed Coating as Delivery for Biocontrol Against Fusarium graminearum

Abstract: The commercial use of the entomopathogenic fungi Metarhizium spp. in biopesticides has gained more interest since the discovery that several species of this genus are able to colonize roots. In general, commercial products with Metarhizium are formulated based on conidia for insect pest control. The process of mass production, harvesting, and formulation of infective conidia can be detrimental for conidial viability. Entomopathogenic fungi such as Metarhizium spp. are able to produce high concentrations of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…MS formation is artificially induced in entomopathogenic fungi and yield varies with the carbon concentration as well as the C:N ratio of liquid media (Jaronski and Jackson 2012 ). The yield obtained in the present work (10 3 MS/mL) was similar to those reported by Rivas-Franco et al ( 2020 ) for the isolate F99 of M. novozealandicum with ∼1 × 10 3 MS/mL and those reported for other species from the same genera such as M. anisopliae, M. robertsii and M. acridum , which reached maximum yields between 7.0 × 10 3 and 1.1 × 10 4 MS/mL (Mascarin et al 2014 ). Similar yields were also reported for the entomopathogenic fungi B. brongniartii and B. bassiana with 1.1 × 10 3 and 3.8 x 10 3 MS/mL, respectively (Villamizar et al 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MS formation is artificially induced in entomopathogenic fungi and yield varies with the carbon concentration as well as the C:N ratio of liquid media (Jaronski and Jackson 2012 ). The yield obtained in the present work (10 3 MS/mL) was similar to those reported by Rivas-Franco et al ( 2020 ) for the isolate F99 of M. novozealandicum with ∼1 × 10 3 MS/mL and those reported for other species from the same genera such as M. anisopliae, M. robertsii and M. acridum , which reached maximum yields between 7.0 × 10 3 and 1.1 × 10 4 MS/mL (Mascarin et al 2014 ). Similar yields were also reported for the entomopathogenic fungi B. brongniartii and B. bassiana with 1.1 × 10 3 and 3.8 x 10 3 MS/mL, respectively (Villamizar et al 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…M. novozealandicumwas also pathogenic to grass grub (C. giveni) reaching 69.2% efficacy at 21 days post challenge, similar to the level of control reported by Glare (1994), where 60% mortality caused by M. anisopliaeby day 35 after inoculation was observed. Rivas-Franco et al (2019) also reported similar mortalities, with values up to 67% when using M. anisopliae and up to 55% when using M. novozealandicumas a seed coating on maize seeds. The isolate AgR-F177 was demonstrated to be pathogenic against DBM but the efficacy only reached 45.7%, suggesting low virulence against this insect when compared with other fungal species such as Beauveria bassiana, Metarhizium rileyi and Isaria sinclairiithat can reach between 80% to 100% mortality (Duarte et al 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Their endophytic behaviour allows them to colonise plant-derived substrates, affecting plant-volatile emissions during insect infestations [ 102 ]. Plant-derived substrates, such as rice grains, can be used for mass production and formulation of EFs [ 103 , 104 ].…”
Section: Multitrophic Interactions Of Entomopathogenic Fungi Crops An...mentioning
confidence: 99%
“…These fungi also produce resting structures known as sclerotia, which can help them survive in adverse environmental conditions. The colony morphology of these fungi can vary depending on the growth conditions [28,29].…”
Section: Introductionmentioning
confidence: 99%